2016
DOI: 10.1080/10298436.2016.1175563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low temperature viscoelastic properties and fracture behavior of bio-asphalt mixtures

Abstract: The overall national emphasis on sustainability in pavement construction has led to the promotion of recycled materials such as reclaimed asphalt pavement (RAP) and reclaimed asphalt shingles. In general, the inclusion of these materials has led to reduced performance at low temperatures leading to thermal cracking. Previous research by the authors showed that the application of bio-binder from swine manure could alleviate the effect of RAP while improving the overall low temperature bulk viscoelastic and frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Wood, miscanthus, and corn stover-based bio-oils were introduced into a neat asphalt for fabrication of asphalt mixtures with and without RAP. From disc-shaped compacted tension fracture (DCT) and indirect tension (IDT) tests at low temperatures, it was shown that the bio-based modifiers improve the low-temperature physical properties with regard to fracture and creep compliance of mixtures without RAP and mitigate the detrimental effects of RAP at low-temperature performance [181].…”
Section: Bio-binder Modifiers (Bbm)mentioning
confidence: 99%
“…Wood, miscanthus, and corn stover-based bio-oils were introduced into a neat asphalt for fabrication of asphalt mixtures with and without RAP. From disc-shaped compacted tension fracture (DCT) and indirect tension (IDT) tests at low temperatures, it was shown that the bio-based modifiers improve the low-temperature physical properties with regard to fracture and creep compliance of mixtures without RAP and mitigate the detrimental effects of RAP at low-temperature performance [181].…”
Section: Bio-binder Modifiers (Bbm)mentioning
confidence: 99%
“…The fast pyrolysis product bio‐oil in particular has been investigated as a bio‐based asphalt binder, with laboratory test results finding that its addition can reduce mixing temperatures and improves high temperature performance while reducing low temperature performance . The reduced low temperature performance is offset by the ability to introduce a higher reclaimed asphalt pavement content into asphalt containing bio‐oil . Bio‐oils derived from corn stover, waste wood, switchgrass, and oak have all been identified as having performance properties that are similar to and comparable with petroleum‐based asphalt binders.…”
Section: Opportunities For Bio‐based Productsmentioning
confidence: 99%
“…67 Th e reduced low temperature performance is off set by the ability to introduce a higher reclaimed asphalt pavement content into asphalt containing bio-oil. 68 Bio-oils derived from corn stover, 69 waste wood, 67 switchgrass, 70 and oak 71 have all been identifi ed as having performance properties that are similar to and comparable with petroleum-based asphalt binders.…”
Section: Asphaltenesmentioning
confidence: 99%
“…To make the binder specimen, the asphalt binder is poured into the aluminum mold wrapped in Teflon tape and placed on the granite slab, which is heated to the temperature of 135 • C, see Figure 4a. Prepared binder samples are allowed to cool down to room temperature for two hours before conducting the corresponding AE tests [31][32][33][34][35][36][37]. Figure 4b shows the specimen after being tested using AE.…”
Section: Acoustic Emission Based Evaluation Of Embrittlement Temperatmentioning
confidence: 99%
“…The signals were then digitized using a 16-bit analog to digital converter (ICS 645B-8) using a sampling frequency of 2 MHz and a length of 2048 points per channel per acquisition trigger. The outputs were stored for later processing using Digital Wave software (Wave-Explorer TM V7.2.6) [9,[31][32][33][34][35][36][37]. The Embrittlement Temperature (T EMB ) of asphalt materials is defined as the temperature corresponding to the first high-energy AE event above a chosen energy threshold.…”
Section: Testing Asphalt Bindersmentioning
confidence: 99%